2001
DOI: 10.1002/dc.2033
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of ThinPrep and TriPath PREP liquid‐based preparations in nongynecologic specimens: A pilot study

Abstract: ThinPrep (TP) and TriPath PREP (TriP) are two liquid-based cytologic preparations that produce a thin layer of cells. This study compares the diagnostic accuracy and different cytomorphologic alterations produced by these preparations in nongynecologic specimens. Samples from 10 urines (3 urothelial carcinomas and 7 negative), 4 positive serous fluids, and 7 fine-needle aspirates (FNAs) were prepared by both techniques. FNAs represented one each of: Hashimoto's thyroiditis (HT), hyperplastic colloid nodule (HC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
85
0
3

Year Published

2006
2006
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(95 citation statements)
references
References 16 publications
7
85
0
3
Order By: Relevance
“…This structural alteration was demonstrated in both benign and malignant breast lesions in the current study (p < 0.001, respectively). Although there is no comparable previous study of SP-based breast cytology, three-dimensional configurations of cell clusters have been observed in a few studies of nongynecologic FNACs [22,23]. Jung et al [23] reported that the SP procedure showed an increase in clustered tissue fragments that caused difficulty in the assessment of nuclear features compared with CS in thyroid FNAC.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…This structural alteration was demonstrated in both benign and malignant breast lesions in the current study (p < 0.001, respectively). Although there is no comparable previous study of SP-based breast cytology, three-dimensional configurations of cell clusters have been observed in a few studies of nongynecologic FNACs [22,23]. Jung et al [23] reported that the SP procedure showed an increase in clustered tissue fragments that caused difficulty in the assessment of nuclear features compared with CS in thyroid FNAC.…”
Section: Discussionmentioning
confidence: 95%
“…Considering the technical aspects of SP preparation, in our opinion, the presence of cell groups arranged in three-dimensional clusters might be a characteristic finding of the LBP method. In a valuable analysis comparing SP and TP, Michael et al [22] described a prominent three-dimensional configuration in SP compared with considerable flattening of cell clusters with the TP method. The authors mentioned that this is probably due to the discriminative methodology of the two preparations, while the SP-based preparation is processed by simple sedimentation of cells on the slide without compression, TP involves positive pressure applied to the cylinder during cell transfer that results in true monolayer sheets [22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The conclusion of this study was that SP seemed superior to TP in FNA specimens where preservation of architecture and cellular integrity were important considerations [32]. …”
Section: Comparison Of Tp Sp and Cytospin Preparations In Various Spmentioning
confidence: 99%
“…For example, diagnostic cells are famously smaller in TP. [3][4][5] In thyroid cytology, several alterations have been reported, including reduction and alteration in colloid, decreased pseudo-inclusions in cases of papillary cancer, and difficulty recognizing Hashimoto thyroiditis in TP compared with CPs. 3,6 Despite these alterations, several large studies have proven that TP is at least equivalent to CPs in diagnostic accuracy and is a safe alternative to CPs in thyroid cytology.…”
mentioning
confidence: 99%